Pengaruh Literasi Digital, Locus of Control, dan Hasil Belajar Kewirausahaan terhadap Perilaku Berwirausaha Mahasiswa - Divana Aghata Kurnia Dewi; Susanti Susanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this research is to analyze and examine the impact of digital literacy, locus of control, and entrepreneurial learning outcomes on entrepreneurial behavior in students of the Faculty of Economics, State University of Surabaya. The research carried out is included in quantitative method. Sample used in this research is 71 students selected and determine on purposive sampling technique. Analyze and processed the data is using multiple linear regression. Same with data analysis, the digital literacy, locus of control, and entrepreneurship learning outcomesvariable have a simultan influence on the entrepreneurial behavior of students of the Faculty of Economics, State University of Surabaya. Entrepreneurship learning outcomes.